Review: Responsible use of technology to combat Cyberbullying among adolescents - Chintha Kaluarachchi (Australasian Journal of Information Systems, 2020)
Cyberbullying has become a major challenge for authorities, parents, guardians and schools in particular, especially in the era of the digital world. This paper reviews available empirical research to examine the issues such as the responsible use of technology amongst young people, parents and schools responsibility to protect against Cyberbullying. The analysis revealed that the responsible use of technology provides better practices to encourage comparisons because of these new digital technologies. Parents and educators are the key to Cyber ethics, therefore teaching the responsible use of technology whilst focusing on Cyber ethics at the start of young people’s exposure to technology use may be an excellent strategy to reduce the growth and impact of Cyberbullying. The paper will also review good practices for young people, school communities and parents to prevent and manage Cyberbullying and unethical behaviours online. These claims are examined using current literature to ensure a better understanding of responsible use of technology and understanding of Cyberbullying in order to support young people to combat this immerging societal challenge.